Conceptual framework for risk communication between emergency response team and management team at healthcare facilities: A Malaysian perspective - Ab Aziz, Nur Farhani; Akashah, Farid Wajdi; Abdul Aziz, Aniza (Elsevier, 2019)
The requirement to establish a Disaster Risk Management Plan (DRMP) and Emergency Response Team (ERT) in Malaysia is stated in the Occupational Safety and Health Act 1994. DRMP provides first responder such as ERT a standard operating procedure (SOP) when assisting evacuation and performing search and rescue. In performing such tasks, ERT requires sufficient information outline in the DRMP and other risk communication activities that are conducted by the management team. However, past fire incidents at public hospitals in Malaysia shows that the current practice of risk communication at public hospitals does not facilitate the ERT's decision-making process. This paper intends to propose a conceptual framework of risk communication that can guide the management team at public hospitals in delivering information regarding fire safety to the ERT to ensure its effectiveness. Standards on disaster risk management, public hospital's contingency plans, and past research were reviewed. This framework provides an overall idea of how the decision-making process is made among the ERT members. This shows the involvement of risk communication and risk perception that can affect the ERT's judgement and actions taken during the response phase. Findings of this paper include factors that address people's perception towards risk and elements of risk communication that should be considered to develop and improve risk communication policy. © 2019